Вплив стану експресії ядерних рецепторів статевих стероїдних гормонів в ендометрії на репродуктивну функцію жінки - Авраменко, Наталія Вікторівна; Кабаченко, Олена Володимирівна; Максименко, В. Г.; Барковський, Дмитро Євгенович; Авраменко, Н. В.; Кабаченко, Е. В.; Барковский, Д. Е.; Avramenko, N. V.; Kabachenko, O. V.; Maxymenko, V. G.; Barkovsky, D. Ye. (Запорізький державний медичний університет, 2015)
З метою дослідити вплив стану рецепторів стероїдних статевих гормонів ендометрія на репродуктивну функцію жінки в порівнянні з даними УЗД, гістероскопії і гістологічного дослідження та гормональним тлом для підвищення ефективності діагностики та відновлення ендометрія обстежили 50 жінок віком від 23 до 52 років із гіперплазією ендометрія, яких поділили на 3 рандомізовані групи: I – 20 жінок із первинним безпліддям, II – 13 жінок із вторинним безпліддям, III – 17 жінок без безпліддя; виконали аналіз експресії ядерних рецепторів стероїдних гормонів в ендометрії. Використані гістероскопія, УЗД, анамнестичний, клініко-лабораторний, гістологічний методи, досліджене гормональне тло (ФСГ, ЛГ, пролактин, естрадіол, вільний тестостерон); експресію рецепторів естрогенів і прогестерону у стромі та залозах оцінювали за методом Histochemical score. Під час гіперплазії ендометрія спостерігається пригнічення рецепторів естрогенів і в меншому ступені рецепторів прогестерону на тлі гіпоестрогенемії, гіперпролактинемії, гіперандрогенемії. С целью изучить влияние состояния рецепторов стероидных половых гормонов эндометрия на репродуктивную функцию женщины в сравнении с данными УЗИ, гистероскопии и гистологического исследования и гормональным фоном для повышения эффективности диагностики и возобновления эндометрия обследовали 50 женщин в возрасте от 23 до 52 лет с гиперплазией эндометрия, разделённых на 3 рандомизированные группы: I – 20 женщин с первичным бесплодием, II – 13 женщин со вторичным бесплодием, III группа –17 женщин без бесплодия; проведён анализ экспрессии ядерных рецепторов стероидных гормонов в эндометрии. Использованы УЗИ, гистероскопия, анамнестический, клинико-лабораторный, гистологический методы, исследован гормональный фон (ФСГ, ЛГ, пролактин, эстрадиол, свободный тестостерон); экспрессию рецепторов эстрогенов и прогестерона в строме и желёзах оценивали методом Histochemical score. При гиперплазии эндометрия наблюдается угнетение рецепторов эстрогенов и в меньшей степени рецепторов прогестерона на фоне гипоэстрогенемии, гиперпролактинемии, гиперандрогенемии. Background. In recent years, rate of hyperplastic processes of reproductive system that relate to the common genital pathology in women of all age groups increased and ranges from 17 to 59% of all gynecological pathology. Recent studies have shown that the functional state of the endometrium is determined by the number of endometrial tissue receptors to corresponding steroid hormones. Objective. To explore the state of steroid hormones receptors in endometrial hyperplasia in compare with ultrasound, hysteroscopy and histological and hormonal background data research to improve diagnosis and recovery endometrium state. Methods. medical history analysis, clinical laboratory analysis, ultrasound diagnostics, hysteroscopy, histological methods. Hormones levels (FSH, LH, prolactin, estradiol, free testosterone), and expression of estrogen and progesterone receptors in the stroma and glands was evaluated by Histochemical score. Results. 50 women of 23–52 years with hyperplasia of endometrium, were divided into 3 randomized groups: I – 20 women with primary infertility, II – 13 women with secondary infertility, III – 17 women without infertility. Early sexual activity was almost twice as often observed in the first two groups of women (respectively 61.54%, 60.00%) against 29.41% in the third group. Gynecological history was weighed almost all three groups of women with chronic bilateral salpingoophoritis, obesity (I gr. – 85%, II in December. – 76.92%, III gr. – 76.47%). Uterine leiomyoma found in every second woman III gr. – 9 (52.94%, p <0.05), 3 women (15%). At primary infertility there was US endometrial hyperplasia in every from four women, endometrial thickness less than the corresponding day of the cycle, which may indicate a lack of estrogen effect on the endometrium. In secondary infertility hyperplasia was detected in 14.29% of cases, in the third group – 7.14%. Estrogen (more) and progesterone (less) receptors level inhibition on the background of the hypoestrogenemia, hyperprolactinemia, hyperandrogenemia were detected. Conclusions 1. Risk factors for endometrial hyperplasia were: early sexual life, chronic salpingoophoritis, uterine leiomyoma. 2. Estrogen and progesterone receptor inhibition were detected on the background of the hypoestrogenemia, hyperprolactinemia, hyperandrogenemia in patients with endometrial hyperplasia.
Влияние состояния экспрессии ядерных рецепторов стероидных гормонов в эндометрии на репродуктивную функцию женщины
Expression level of nuclear steroid hormone receptors in endometrium influence on female reproductive function
Keywords: репродукція; статевих залоз гормони; ендометрій; репродукция; половых желёз гормоны; эндометрий; Reproduction; Sex Glands Hormons; Endometrium